ANALISIS TINGKAT PERPUTARAN PIUTANG TERHADAP PENGENDALIAN INTERNAL PADA PT. PANAIKANG MOTOR PERKASA DI MAKASSAR - Indrawan Azis; Andi Harnezia Nizela (AkMen JURNAL ILMIAH, 2015)
The title of research was discussed on November 19th , 2014 and has been approved to do research on PT. Panaikang Motor Perkasa road A.P Pettarani number 21. The time used for this study is approximately two months. Receivables are accrued revenue due to credit sales transactions . Receivables that are too large can hurt the company, because working capital is embedded in the accounts is too large will result in reduced liquidity of the company. The primary objective of this study was to determine the level of accounts receivable turnover to internal control at PT. Panaikang Motor Perkasa. This study used a descriptive quantitative analysis method, the method of analysis in testing the accounts receivable turnover rate is receivable turnover (RTO), Average collection period (ACP), and ratio of ratio of arrears billing will then be compared with the internal control over accounts running on PT. Panaikang Motor Perkasa. The results obtained from this study is the accounts receivable turnover rate in PT. Panaikang Motor Perkasa relatively slow in Makassar Calculations RTO decreased from the year 2009 to the year 2010, which exceeds the ACP calculation of the average standard set time billing company, the calculation of the ratio of arrears and billing ratio shows the number of the nominal value of the receivables in arrears major in 2010, as well as internal controls for receivables that have not been going well caused because too many policies and lack of monitoring of management's internal controls over accounts receivable